Rücktitelbild: Bor‐Zentrierte Lewis‐Supersäuren durch Redoxaktive Liganden: Anwendung in der C‐F‐ und S‐F‐Bindungsaktivierung (Angew. Chem. 13/2023). (6th March 2023) - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan
Abstract : One‐electron oxidation converts the ferrocene‐substituted borane into a Lewis superacid, as reported by Frank Breher, Jan Paradies, and co‐workers in their Communication (e202216959) . The Lewis superacid activates almost inert carbon–fluorine and sulfur–fluorine bonds for reductions, alkylations, and arylations to form new chemical bonds.